2012
DOI: 10.1021/jp303966u
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Oxygen Reduction Reaction on Pt3Ni Alloy Fuel Cell Cathode

Abstract: We use quantum mechanics, density functional theory at the PBE level, to predict the binding-site preferences and reaction barriers for all intermediates involved in the oxygen reduction reaction (ORR) on the low energy surface of Pt 3 Ni alloy. Here we calculate that the surface layer is Ni depleted (100% Pt) while the second layer is Ni enriched (50% Pt) as shown by experiment. Even though the top layer is pure Pt, we find that the sublayer Ni imposes strong preferences in binding sites for most intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 36 publications
3
78
0
Order By: Relevance
“…The sublayer Ni of Pt 3 Ni alloy, the "most optimal ORR electrocatalyst" ever reported, imposes strong preferences in binding sites for most intermediates, which in turn strongly inuence the reaction barriers. 51 Stephens et al 52 also conrmed that the presence of subsurface 3d metals can weaken the binding of a Pt surface to OH*. They concluded that only a slight weakening of DE OH* by $0.1 eV, relative to Pt (111), will lead to optimal activity for ORR, resulting in an 8-fold improvement in the oxygen reduction activity.…”
Section: Catalyst Designmentioning
confidence: 99%
“…The sublayer Ni of Pt 3 Ni alloy, the "most optimal ORR electrocatalyst" ever reported, imposes strong preferences in binding sites for most intermediates, which in turn strongly inuence the reaction barriers. 51 Stephens et al 52 also conrmed that the presence of subsurface 3d metals can weaken the binding of a Pt surface to OH*. They concluded that only a slight weakening of DE OH* by $0.1 eV, relative to Pt (111), will lead to optimal activity for ORR, resulting in an 8-fold improvement in the oxygen reduction activity.…”
Section: Catalyst Designmentioning
confidence: 99%
“…O hydration has a lower barrier than direct OH formation (O ad + H ad → OH ad ) for pure Pt, making it the more relevant reaction to study. In the case of Pt alloys when the surface is 100% Pt but the second layer is not, the O hydration barrier was lower than direct OH formation (0.34 eV vs. 0.57 eV for Pt 3 Ni ) 3 . Therefore, O hydration is the more relevant reaction to study for the case of Pt-M-Pt sandwiches due to the 100% Pt surface which has shown a preference for O hydration over direct OH formation.…”
Section: H 2 O Formation: There Is Only One Reaction (8)mentioning
confidence: 85%
“…Pure Pt appears to have a too low oxo-asymmetry index value and appears to be limited in process II as it was shown in our previous work. 3,4 Pt-Pd-Pt, Pt-Ir-Pt, and Pt-Rh-Pt need to be moved more to the upper left which also means improving process II of the ORR. Pt-Os-Pt needs to be moved more down which means process III, H 2 O formation, limits the ORR.…”
Section: Overlap = D-dos(-593)+d-dos(-435)+d-dos(-377)+d-dos(-067mentioning
confidence: 99%
See 2 more Smart Citations